PENGARUH MODEL DISCOVERY LEARNING BERBANTUAN MEDIA BOX TO THE WORLD OF INTELLIGENCE TERHADAP KETERAMPILAN MENULIS SISWA SD - Latifatul Mutoharoh, Dhenok; Hawa, Anni Malihatul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The problem addressed in this study is the low level of writing skills among third-grade elementary school students. This study aims to determine the differences in and the influence of the Discovery Learning model supported by